Kajian Makna Kata Simbolik “Mulak Ari” dalam Marhata-Hata pada Adat Tradisi Pernikahan Batak Mandailing - Eka Indriyani; Rosmawaty Harahap; Elly Prihasti Wuriyani (Medan Resource Center, 2022)
Tradition is one of the habits passed down from generation to generation by a group of people based on developing cultural values. The number of traditions that develop in each region is a culture that has been successfully preserved so that future generations will still know how the traditions and culture of certain tribes or ethnicities are. In this paper, the author aims to provide an understanding and description of the study of oral traditions owned by the Mandailing Tribe. The form of tradition discussed in this study is the Batak Mandailing Marhata-Hata Marriage Tradition: